Architectural houses - Asensio Cerver, Francisco (Barcelona : Ediciones Atrium S A, 1991)
V.1. - City houses -- V.2. - City houses V.3. - Houses by the sea -- V.4. - Houses by the sea -- V.5. - Houses by the sea -- V.6. - Country houses -- V.7. - Country houses -- V.8. -- V.9. - Houses in the mountains -- V.10. - Houses in the high mountains